Persepsi Interpersonal Yang Terjadi Akibat Media Sosial Diera Digital (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Interpersonal perception has undergone a significant transformation in the digital era, especially through the influence of social media. The presence of social media has now influenced the way individuals understand, interact, and form interpersonal relationships. The writing in this journal uses descriptive qualitative research methods, namely research conducted to examine an object, a condition, a group of people, or other phenomena with natural or real conditions (without experimental situations) to create a systematic overview or detailed description that is factual and accurate. This research is a study intended to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions or thoughts of people individually or in groups through observation and literature study so that a complete picture of an event can be presented which is intended to expose and clarify a phenomenon that occurs. From the discussion of interpersonal perceptions that occur due to social media in this digital era, it can be related to several theories of communication psychology, namely informative theory and behaviorism theory.